2016
DOI: 10.1039/c6tc01750a
|View full text |Cite
|
Sign up to set email alerts
|

Ultraviolet and blue cathodoluminescence from cubic Y2O3and Y2O3:Eu3+generated in a transmission electron microscope

Abstract: The investigation of cubic spherical submicron particles of non-doped Y2O3and Y2O3doped with Eu3+in a TEM using CL from individual particles is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 31 publications
(72 reference statements)
1
11
0
Order By: Relevance
“…This spectrum shows only the intrinsic blue emission of cubic Y 2 O 3 between 400 and 500 nm upon excitation with high energetic electrons. 21 From this spectrum it can be concluded that the large spherical particle did not contain the Eu-dopant; routinely a strong Eu 3+ emission would be observed from this sized particle. Another indication that this particle must be cubic Y 2 O 3 is the fact that 2% Eu 3+ will almost quench the intrinsic Y 2 O 3 emission.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…This spectrum shows only the intrinsic blue emission of cubic Y 2 O 3 between 400 and 500 nm upon excitation with high energetic electrons. 21 From this spectrum it can be concluded that the large spherical particle did not contain the Eu-dopant; routinely a strong Eu 3+ emission would be observed from this sized particle. Another indication that this particle must be cubic Y 2 O 3 is the fact that 2% Eu 3+ will almost quench the intrinsic Y 2 O 3 emission.…”
Section: Resultsmentioning
confidence: 88%
“…Another indication that this particle must be cubic Y 2 O 3 is the fact that 2% Eu 3+ will almost quench the intrinsic Y 2 O 3 emission. 21 The mere presence of this intrinsic emission is thus a proof that the particle is undoped Y 2 O 3 precursor. The evidence presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The details of this method have been described in Refs. 21,19. We have applied this method for the determination of the energy efficiency of the CL of the phosphors mentioned in the experimental section.…”
Section: Materials and Synthesis-powder Samples Of Y 3 Al 5 O 12 :Gd 3+mentioning
confidence: 99%
“…Finally, the combination of microscopy and spectrometry in a transmission electron microscope (TEM) will be presented [21,22,23]. The JEOL TEM of Brunel University London was, when it was delivered, a unique instrument being equipped with a Vulcan TM CL detector of Gatan (Pleasanton, CA, USA) for imaging (panchromatic) and spectroscopic purposes.…”
Section: Introductionmentioning
confidence: 99%